Molecular model of cyclin-dependent kinase 5 complexed with roscovitine - de Azevedo, W. F.; Gaspar, R. T.; Canduri, F.; Camera, J. C.; da Silveira, NJF (Elsevier B.V., 2002)
Here is described a structural model for the binary complex CDK5-roscovitine. Roscovitine has been shown to potently inhibit cyclin-dependent kinases 1, 2 and 5 (CDK1, 2, and 5), and the structure of CDK2 complexed with roscovitine has been reported; however, no structural data, are available for complexes of CDK5 with inhibitors. The structural model indicates that roscovitine strongly binds to the ATP-binding pocket of CDK5 and structural comparison of the CDK2-roscovitine complex correlates the structural differences with differences in inhibition of these CDKs by this inhibitor. This structure opens the possibility of testing new inhibitor families, in addition to new substituents for the already known lead structures of adenine derivatives. (C) 2002 Elsevier B.V. (USA). All rights reserved.
Keywords: CDK; Roscovitine; bioinformatics; Structure; drug design